No todo lo que brilla es oro: apuntes sobre la naturaleza del sinarquismo mexicano (Tzintzun, Revista de Estudios Históricos, 2016)
he present paper discusses the deinition of fascism used by the historianJean Meyer in his book entitled El sinarquismo, el cardenismo y la iglesia 1937-1947. By providing a quick overview of existing research on the subject, itpoints out the great variety of deinitions and points of view based on variousstudies. In order to address the question of the fascist character of synarchism,the paper suggests a close look at the discourse of the Unión NacionalSinarquista. he present study takes the perspective of the common denominatorsof fascism and relies on Hélgio Trindade’s work on Brazilian integralismand investigates those points of the synarchist ideological discoursewhich allow us to relativize and discuss critically why Jean Meyer excludedsynarchism from the list of fascist movements.
Keywords: fascism; synarquism; Mexico 20th century; integralism; Unión Nacional Sinarquista